Childhood with Bourdieu
X, 225 p.
Keywords: This collection is an engaging exploration of how Bourdieu's key concepts - field, habitus and capital - help us re-think the status of childhood. The authors are committed to improving the social status and well-being of childhood in social, economic and political worlds that too often fail to accord children respect for their human rights.